This way for pain: subculture, witness and tattoo artists in the Northern suburbs of Johannesburg - Preston-Monzon, Kristen (My University, 2023)
This is a study of women and their experiences working in the tattoo industry by looking at the relations of gender, subculture and white privilege, as well as the location of Johannesburg, where the research is based. White men dominate the tattoo industry in the Northern Johannesburg suburbs of Douglasdale and Blairgowrie. However, this has been changing as the subculture of tattoos begins to become less and less exclusive. As more women and different ethnicities join the evolving subculture that is the industry, you find a pushback by the “classical” ideals propagated by the nostalgia of being the “other” or feelings of rejection from the ”norm.” These feelings have always been a part of the tattoo artist subculture in South Africa. Through formal interviews with tattoo artists and employees at two studios and through observations, note taking and audio recordings, I found that although it is still a field dominated by white men, not only is the field of having and making tattoos itself changing, but it is also becoming more accepted into mainstream society. Here women artists can create their own spaces and become accepted into the industry, even though some still face discrimination and harassment.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Gender; Whiteness; Race